2017
DOI: 10.5217/ir.2017.15.2.236
|View full text |Cite
|
Sign up to set email alerts
|

Colonic dysmotility and morphological abnormality frequently detected in Japanese patients with irritable bowel syndrome

Abstract: Background/AimsColonoscopy and computed tomography (CT) are used primarily to exclude organic diseases in patients with irritable bowel syndrome (IBS), rather than to assess the pathophysiology of IBS. We aimed to evaluate colonic dysmotility and morphology in Japanese patients with IBS.MethodsOne hundred eighty-four patients with IBS and 49 asymptomatic controls who underwent colonoscopy in combination with CT colonography or barium enema were retrospectively reviewed between 2008 and 2012. Water-aided colono… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
4
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 29 publications
0
4
0
2
Order By: Relevance
“…Weak recommendation, evidence level B, 100% agreed. Comment: Colonoscopy offers diagnostic value to identify IBS patients and provide supportive evidence of pathophysiology compatible with IBS due to visceral hypersensitivity during colonoscopy as well as colonic dysmotility, with the additional benefit of excluding organic disease [ 63 , 64 ]. Diagnostic colonoscopy in 4178 undiagnosed IBS patients showed that there were no differences in regard to the prevalence of organic colonic diseases between patients who did and did not fulfill the Rome III criteria, suggesting that these criteria cannot exclude organic colonic lesions [ 65 ].…”
Section: Diagnosismentioning
confidence: 99%
“…Weak recommendation, evidence level B, 100% agreed. Comment: Colonoscopy offers diagnostic value to identify IBS patients and provide supportive evidence of pathophysiology compatible with IBS due to visceral hypersensitivity during colonoscopy as well as colonic dysmotility, with the additional benefit of excluding organic disease [ 63 , 64 ]. Diagnostic colonoscopy in 4178 undiagnosed IBS patients showed that there were no differences in regard to the prevalence of organic colonic diseases between patients who did and did not fulfill the Rome III criteria, suggesting that these criteria cannot exclude organic colonic lesions [ 65 ].…”
Section: Diagnosismentioning
confidence: 99%
“…[2], bağırsak semptomları ile kolonik transit zamanı ve kolon uzunluğu arasındaki ilişkiyi araştırdıkları çalışmalarında, transit zamanı ile kolon döngü sayısı arasında doğrudan iliş- ki bulmuştur. Yapılan çalışmalarda morfolojik anomaliler, irritabl bağırsak sendromu olan hastalarda asemptomatik kontrol grubuna göre daha sık bulunmuştur [23,24].…”
Section: Discussionunclassified
“…Kolondaki redundansinin rutin klinik uygulamalarda önem kazandığı diğer bir hasta grubu, optik kolonokospi ile değerlendirilecek hastalardır. Kolon anomalileri optik kolonoskopiyi zorlaştırmakta ve süresini uzatmaktadır [23]. Özellikle kolondaki kıvrımlı yapı ("tortuosity") ve redundansi, çekumun görüntülenmesini zorlaştırıcı faktörlerdendir [11,27,28].…”
Section: Discussionunclassified
“…1) In diarrhea-predominant IBS (IBS-D), which is one of the classifications, increased intestinal peristalsis has been reported. 2) Therefore, intestinal peristalsis inhibitors are used in the treatment of IBS-D. 1) Hyoscine butylbromide and other drugs are sometimes used to suppress peristalsis, but their use is limited owing to adverse events and insufficient effectiveness. 1,3,4) The use of Kampo medicines for the treatment of IBS has also been mentioned, and one Kampo medicine, keishikashakuyakuto, has been reported to significantly suppress abdominal pain in patients with IBS-D compared to placebo.…”
Section: Introductionmentioning
confidence: 99%